COMPARATIVE ANALYSIS OF ANDROID-BASED ONLINE TRANSPORTATION APPLICATION SECURITY USING MOBILE SECURITY FRAMEWORK (MOBSF) - Subakja, Triyawan Bagus; Fronita, Mona; Syaifullah, Syaifullah; Ahsyar, Tengku Khairil; Siregar, Syafril (STKIP PGRI Tulungagung, 2025)
Online transportation is a service provided over the internet, representing a technological innovation that has significantly facilitated travel for Indonesians. These applications have gained widespread adoption in Indonesia, serving as alternatives to conventional transport modes like taxis and traditional motorcycle taxis. They offer convenience and speed in booking rides, along with secure transactions through digital payment systems. Despite the user-friendly experience and advantages offered by these applications, their security cannot be overlooked. The increasing accessibility of Android-based online transportation applications has made them a prime target for malicious actors (